Experimental determination of forced convective heat transfer coefficient with nanofluid in a plain tube - Mohd Fahmi, Jasni (2012)
Nowadays, lots of industrial and consumer product have heat transfer as their most vital process. But there is a limit of the heat transfer due to the inherently poor thermal performance of conventional fluids and restricted in developing energy efficient heat transfer fluids. With the strong need from industry force the need to build up superior heat transfer fluids with considerably higher thermal performance than are presently available. Hence, lots of research has been made by the scientists and engineers to break this fundamental limit by dispersing metallic and non-metallic nanoparticles in liquids. There are two ways to prepare nanofluid which is two step method and dilution process. In this study, the process that used to prepare the nanofluids is dilution process. TiO water based nanofluid was prepared at four different concentrations 1%, 1.5%, 2% and 3%. The experiment was conducted for the estimation of heat transfer coefficient (htc) of the nanofluids at constant heat flux and various Reynolds number from 10,000 to 30,000. The experiment was started with distilled water for validation of experiment set up. Additions of the nanoparticles to the water increase their heat transfer coefficient with maximum enhancement of 13.6% compared with pure water at 1.5% volume percentage. Experimental result were compared with previous result in literature study and found consistent with considerable deviation observed.